Chemical constituents, in vitro antioxidant and antimicrobial properties of ethyl acetate extract obtained from Cytisus triflorus l'Her. Issue 11 (2nd June 2020) - Benabderrahmane, Wassila; Amrani, Amel; Benaissa, Ouahiba; Lores, Marta; Lamas, J. Pablo; de Miguel, Tinidad; Benayache, Fadila; Benayache, Samir
Abstract: The present study investigates the phenolic composition, antioxidant and antimicrobial activities of an ethyl acetate extract from C. triflorus L'Her. The phytochemical study on the aerial parts of C. triflorus belonging to the Fabaceae family led to the isolation and structural elucidation of 5-Hydroxy-7-O-glucosylflavone (P1), 5-Hydroxy-7-O-galactosylflavone (P2), 5, 7-Dihydroxy-flavone (P3), 5, 7, 3'-Trihydroxy, 4'-methoxy-flavone (P4). These compounds were identified by 1D and 2D NMR combined analysis as well as by UV. Ethyl acetate extract of C. triflorus showed a significant and dose-dependent antioxidant activity in vitro, related to the presence of phenolics (180.33 ± 12.22 µg GAE/mg) and flavonoids (16.78 ± 1.54 µg QE/mg). The antimicrobial activity was evaluated in vitro against Staphylococcus aureus CECT 240 and Escherichia coli CECT 4099, by agar-diffusion method. The most active antibacterial activity was expressed by ethyl acetate extract of C. triflorus against Gram-positive bacteria S. aureus. The gathered results suggest that C. triflorus polyphenols and flavonoids are closely associated to its antioxidant and antimicrobial properties. Graphical Abstract: